THE EFFECT OF TRAINING, WORK DISCIPLINE AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE AT THE BUILDING PLANT T DEPARTMENT OF TIRE COMPANY IN BANTEN - Aji Kresna Tri Anggara, Abdul; Ruslan, Sangkala (Dinasti Publisher, 2021)
The era of globalization has an impact on changes in various aspects, including business competition which has become increasing tightly. More and more competitors and high business competition require organizations to have high knowledge and abilities to be able to compete. Changes that occur due to globalization require companies to be able to establish strategies related to improving performance. Tire manufacturing in Banten is one of companies which are faced with business competition in which the company has fairly tight competitors. The Building Plant, Department T, is one of the parts in the organizational structure of this tire company, where the department is also required to meet the performance indicators set by the company. Many factors affect employee performance including training, work discipline and organizational commitment. This study aims to determine the effect of training, work discipline and organizational commitment on employee performance in tire companies in Banten. This study uses a quantitative approach with data analysis in testing the measurement model and testing the structural model using SmartPLS version 3.2.7 software. The results show that training has a significant effect on employee performance, work discipline has a significant effect on employee performance, organizational commitment has a significant effect on employee performance, and training, work discipline and organizational commitment has a significant effect on employee performance.